Leveraging brands at music festivals: NOS Alive sponsorship - Trindade, Gonçalo Filipe de Lemos (2017)
The objective of this study is to understand the relation between event image and sponsor image regarding music festivals, more specifically NOS Alive (the renowned Portuguese music festival). This study will try to comprehend if this relation exists and how and if it is affected by experience and event sponsor-fit (mediators). This research is composed by two studies. Pilot study was composed by a survey, that had two hundred and eighty participants and it was conducted in the event NOS Alive, and an interview with a specialist in the area, which allowed the identification of the categories and main concepts to be analyzed in the second study. In the quantitative study, a questionnaire was created and applied, especially at a national level (two hundred and fifty-three answers) with the objective of confirm the findings of the first study and analyze the relations between the categories previously identified. Seven hypotheses were formulated and tested. According with the analysis done on this research, two models were created regarding the sponsor image of NOS (model 1) and Heineken (model 2). The findings indicate that event image affects directly and indirectly NOS image with experience and event sponsor-fit as mediators (model 1). While in model 2, event image just affects indirectly Heineken image with experience and event sponsor-fit as mediators.